2020
DOI: 10.3390/sym12101627
|View full text |Cite
|
Sign up to set email alerts
|

A Trajectory for Advancing the Meta-Cognitive Solving of Mathematics-Based Programming Problems with Scratch

Abstract: It is the intention of the current study to suggest a trajectory for the advancement of prospective mathematics teachers’ use of meta-cognitive skills in solving mathematics-based programming problems with Scratch. Scratch is a code-based program that can be utilized in teaching various disciplines, especially geometry and its rich range of subjects such as the topic of symmetry. The present study suggests that advancing prospective teachers’ meta-cognitive skills in the Scratch environment could be done throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The research results indicate that the preparation resulted in significant differences in the scores of the different constructs, except anxiety, of the acceptance of digital tools for teaching mathematics and science. Thus, the results show the effectiveness of the community of inquiry practices [11,18,22,47,51] regarding the acceptance of technology for teaching, where these practices included synchronous as well as asynchronous means of communication. It is our conclusion that both means are essential in preservice teachers' education [52].…”
Section: -Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…The research results indicate that the preparation resulted in significant differences in the scores of the different constructs, except anxiety, of the acceptance of digital tools for teaching mathematics and science. Thus, the results show the effectiveness of the community of inquiry practices [11,18,22,47,51] regarding the acceptance of technology for teaching, where these practices included synchronous as well as asynchronous means of communication. It is our conclusion that both means are essential in preservice teachers' education [52].…”
Section: -Discussionmentioning
confidence: 85%
“…Especially, they are not or little related to integrating technology in the mathematics classroom. What influenced the pre-service teachers' acceptance of digital tools for teaching is specifically the engagement in negotiating technological knowledge in the forums and as part of the reflection resulted in a teaching context that encourage the pre-service teachers to accept technology as part of their repertoire in the mathematics and science classrooms [11,18].…”
Section: -Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This percentage is relatively not high, but focusing more attention on the factors that cause it could lessen their occurrences and thus lessen the negative affective engagement of the students in their work on online assignments. This could be done by stressing the importance of negotiation and alignment in group work [65,66], which would lead to understanding of the mechanism of group work and thus utilize this mechanism in this group work. In detail, Baya et al [65] found that prospective teachers used negotiation, in the context of a community of practice, as an escalator that supports the decision of in-service mathematics teachers to integrate ICT in the mathematics classroom.…”
Section: Interaction Between the Learner And The Content Overallmentioning
confidence: 99%